PERLINDUNGAN TERHADAP PELANGGARAN HAK ANAK DALAM KELUARGA MENURUT HUKUM HINDU - Kantriani, Ni Ketut (VYAVAHARA DUTA, 2020)
All families crave the birth of a child, especially the hindu family of the birth of a child believed to be able to provide assistance or save the spirit of his ancestors from hell and will perform a tarpana ceremony after his parents die.Â The child is the result of the marriage process. The Book of Manawadharmasasta states that the purpose of marriage includes; Dharmasampatti means that together the husband and wife realize the implementation of dharma, which includes all religious activities and obligations such as carrying out yadnya, because in grehasthalah yadnya can be carried out perfectly. It means to give birth to offspring (sons and daughters) who will continue the mandate and obligation to the ancestors. Through yadnya and the birth of a son suputra, a child will be able to pay off the debt of services to the ancestors (Pitra rna), to the One True God (Deva rna) and to the teachers (Rsi rna), and Rati means to enjoy a sexual life and other sense satisfaction (Artha and Kama) that is not contrary to the Dharma. (Titib,2003:84). From the above quote the purpose of marriage (grehasta dormitory) according to scripture and other Hindu literature is to realize happiness together born and inner and acquire descendants or children who are suputra.Children from the womb until birth have the right and freedom to live and get protection from both their parents, family, society, nation and country. Children in order to grow and develop, then they must be protected by providing nutritious food, proper education, keeping them away from forms of perversion such as acts of violence, discrimination, cruelty, persecution, exploitation, abuse and injustice.Keywords : Protection, Violation, Child Rights, Hindu Law